The Role of Mythological Allusion and Symbolism in Raja Rao’s ‘The Serpent and The Rope’ - Sinha, Dr. Arpana (Journal of Advanced Research in English & Education; Vol 6 No 2 (2021): Journal of Advanced Research in English & Education, 2021)
Raja Rao’s ‘The Serpent and the Rope’ is a work of profound literary and philosophical complexity, woven not with a conventional plot but with a rich tapestry of mythological allusions and symbolism. This article argues that these mythological elements are not mere embellishments but are integral to the novel’s narrative technique, serving as a primary formal device to transcend the mundane and elevate the personal story into a Universal Spiritual epic. The central thesis is that Raja Rao uses this mythic framework to bridge the gap between Ramaswamy’s contemporary life and the timeless wisdom of Advaita Vedanta. Through the detailed analysis of ten key mythological and symbolic elements—including the central metaphor of the serpent and the rope, the spiritual significance of the River Ganges, the archetypal roles of the Guru and the goddesses Sita and Savithri, and the symbolism of light and darkness—the article demonstrates how the novel’s very structure is built upon an ancient, mythic foundation. This use of myth transforms the narrative into a sacred text, where the protagonist’s journey mirrors a timeless, archetypal quest for ultimate truth, thereby providing a cultural and spiritual context essential for understanding the novel’s philosophical core.